Design and Performance Testing of Cranes Lifting Agricultural Equipment and Machinery - Mambela Mambela (JTPG (Jurnal Teknologi Pertanian Gorontalo), 2025)
Handling agricultural machinery and equipment with significant mass requires lifting aids that can enhance efficiency and reduce manual labor. This study aimed to design and test the performance of a lifting crane intended to assist in the lifting and relocation of agricultural machinery. The research involved design, fabrication, and performance testing using incremental loads of 45, 65, 100, 150, 200, 215, and 250 kg. Testing parameters included load mass, lifting time, lifting height, and the structural condition of the crane under load. The results showed that the crane measured 208 cm in length, 87 cm in width, and 195 cm in height, utilizing an HGS-B Micro Electric Rope Hoist motor for the lifting system. Lifting time increased from 7.35 seconds at a 45 kg load to 10.90 seconds at a 250 kg load, while lifting height decreased from 140 cm to 128 cm. Although the crane was capable of lifting loads up to 250 kg, structural bending in the legs began to occur within the 215-250 kg load range. Consequently, the recommended maximum operating load is 200 kg. The study concludes that the designed crane has the potential to serve as a lifting and handling aid for agricultural machinery, provided that load limits and structural integrity are taken into account.